2017
DOI: 10.1371/journal.pone.0189310
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in rats is associated with an increased permeability of the colon to TMA, a gut bacteria metabolite

Abstract: An increased blood trimethylamine N-oxide (TMAO) has emerged as a marker of cardiovascular mortality, however, the mechanisms of the increase are not clear. We evaluated if hypertension was associated with changes in the colon permeability to trimethylamine (TMA), a TMAO precursor. We did experiments on male, 24-26-week-old normotensive Wistar-Kyoto rats (WKY), spontaneously hypertensive rats (SHR) and SHR treated with enalapril, an antihypertensive drug (SHR-E). To check the colon permeability and liver TMA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 29 publications
4
92
0
1
Order By: Relevance
“…Also, in our previous studies we showed an increased concentration of bacterial metabolites in portal and systemic blood in animal models of portal hypertension and systemic hypertension (Jaworska et al, 2017). However, the concentration of bacterial metabolites in the blood depends strongly on gut bacterial composition and their metabolic activity shaped by diet, drugs, etc.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Also, in our previous studies we showed an increased concentration of bacterial metabolites in portal and systemic blood in animal models of portal hypertension and systemic hypertension (Jaworska et al, 2017). However, the concentration of bacterial metabolites in the blood depends strongly on gut bacterial composition and their metabolic activity shaped by diet, drugs, etc.…”
Section: Discussionmentioning
confidence: 85%
“…An increased permeability of the GBB, or a 'leaky gut' , is a pivotal symptom of gut malfunction and is present in numerous intestinal diseases, such as IBD, NEC or acute pancreatitis (Camilleri et al, 2012;Ravisankar et al, 2018;Sonika et al, 2017), and in extra-intestinal diseases, including heart failure (Sandek et al, 2007), hypertension (Jaworska et al, 2017;Santisteban et al, 2017), obesity (Bischoff et al, 2014) and diabetes (Carratu et al, 1999). Therefore, non-invasive evaluation of the GBB might be a promising method for diagnosis and treatment monitoring of diseases associated with GBB malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large body of evidence supports that TMAO is involved in atherosclerosis, the existing body of literature is sparse regarding TMAO and hypertension. Only in HT rats an increased permeability of the colonic gut-blood barrier to TMA, the main TMAO precursor, has been evidenced 47 , but the role of TMAO in HT humans remains unclear.…”
Section: Tmao In Plasma No Significant Differences In Fasting Tmao Cmentioning
confidence: 99%
“…It was explained that TMAO exerted an indirect effect on hypertension via prolonging the hypertensive effect of Ang II, an important hormone in hemodynamic regulation (). Furthermore, hypertension impairs gut–blood barrier and increases intestinal permeability of TMAO to blood circulation, making the situation worse (). These findings may strengthen the positive correlation between elevated plasm levels of TMAO and high risk of atherosclerotic events, which provides a potential reason for the development of hypertension ().…”
Section: The Influence Of Tmao On Risk Factors Of Atherosclerosismentioning
confidence: 99%